EXPLORING AGENCY IN TEACHERS’ IDENTITY CONSTRUCTION THROUGH THE LENS CRITICAL INCIDENT TECHNIQUES - Indaswari, Ragilia; Mbato, Concilianus Laos (ELTR Journal, 2025)
A major increase in empirical and theoretical interest in teacher identity has occurred within the last 20 years. This increase is frequently ascribed to changing perceptions of teachers' roles. Critical incidents affect teachers' development and their professional identity. The issues include how teachers deal with challenging situations in their profession and their sense of agency. This problem can be overcome by educating students to be more assertive in the classroom. This study aims to investigate the professional identities of three in-service EFL teachers through the lens of critical incidents. Three in-service EFL teachers from different regions in Indonesia were purposefully selected as the participants. The main instrument for data collection in this study was the Critical Incident Technique (CIT) by utilizing reflections and in depth-interview to gather the data and ensure triangulation. Respondents voluntarily participated in this research. The result of this research demonstrated that there were 17 codes of CI which were classified into 3 major categories possessed by the participants, namely: students’ behavior, teachers’ reflective practice, and students’ reaction. The strategies teachers use to handle challenging situations in their profession consist of how teachers deal with decision-making, integrating technology, and developing suitable materials.